Examining the association of MMP-1 gene −1607 (2G/1G) and −519 (A/G) polymorphisms with the risk of osteomyelitis: A case-control study. Issue 42 (October 2017) - Kong, Qingzhu; Jin, Yu; Yan, Shi; Wang, Yin; Zhao, Jingxin; Feng, Zhen; Wei, Junqiang; Wang, Yu; Kong, Lingwei; Guo, Litao; Yang, Jianing
Abstract : Abstract: To investigate the effects of matrix metalloproteinase-1 ( MMP-1 ) gene polymorphisms on the onset of osteomyelitis in Chinese Han population. In all, 80 osteomyelitis patients (case group) and 81 healthy people (control group) were recruited into this case-control study. Polymerase chain reaction-restriction fragment length polymorphism method was utilized to examine the genotypes of MMP-1 polymorphisms (−1607 2G/1G and −519A/G) in the 2 groups. Genotype and allele differences between the case and control groups were analyzed by chi-square test. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated to present the association strength between MMP-1 gene polymorphisms and osteomyelitis. Frequencies of −1607 2G/2G genotype between the case and control groups were statistically significant ( P = .025). Compared with 1G/1G genotype carriers, the 2G/2G genotype carriers had 1.605 times risk of developing osteomyelitis (OR 2.605, 95% CI 1.116–6.082). Meanwhile, the 2G allele significantly associated with the risk of osteomyelitis (OR 1.735, 95% CI 1.115–2.701). In addition, frequency of −519GG genotype was obviously higher in case group than that in control group ( P = .024), and GG genotype related to an increased risk of osteomyelitis (OR 2.792, 95% CI 1.127–6.917). Whereas, the −519G allele may be a susceptible factor for osteomyelitis (OR 1.622, 95% CI 1.038–2.536). The MMP-1 −1607 (2G/1G) and −519 (A/G) polymorphisms may contribute to the onset of osteomyelitis.